Integrated methodology of I.I. Mechnikov and modern address immunocorrection at myasthenia - Klimova, E; Drozdova, L; Lavinskaya, E; Bychenko, E (Annals of Mechnikov's Institute, 2020)
Introduction. There is carried out reconstruction of the past in the field of integrated discoveries of well-known scientist I.I. Mechnikov for research of aspects of phagocytic function of immune cells and infectious factors in etiology and pathogenesis of progressing myasthenia. There are analyzed the leading factors which have generated scientific outlook and integrated analytical methodology of knowledge of I.I. Mechnikov – the native of the Kharkov province, the graduate student of the Kharkov Imperial University of 1864, the Nobel prize winner of 1908 for creation of the theory of phagocytosis and the author of set of works in the field of microbiology, immunology and virology. Material & methods. The work studied the mechanisms of disorder of various stages of barrier phagocytic function of neutrophils andfrequencyof occurrence and variousdegreeof expression of virus persistence at patients with myasthenia is determined. Phagocytosis disturbance leads to uncontrollable development of infections at myasthenia. Advance of muscular delicacy and morph-functional disturbances in thymus, obviously, depend on the individual mechanisms which affect various stages of immune disbalance. The whole century has passed from the moment of creation of the phagocytic theory. For this time all stages of this process have been studied, methodical approaches are developed for an estimation of specific features of this phenomenon, from light microscopy to flowing cytofluorometry. Possibilitiesof light microscopy allow to visualize the stages of phagocytosis from chemotaxis and adhesions to completeness of digestion by neutrophils in dynamics. And Nitro Blue Tetrazolium Reduction Test (NBTR) is used for an estimation of enzymatic activity of phagocytes for initiation of formation of active forms of oxygen at the phagosoma formation stage. The given method allows to investigate stages of oxygen-dependent metabolism of neutrophils. Along with these methods of estimation of phagocytosis, which don’t always give the high-grade information about functional condition of phagocyte leucocytes, it is expedient to apply a fluorescent method with use of acridine orange (AO). Results & discussion. Accruing digestion of yeast cells by lysosomic enzymes of neutrophils destabilizes DNAand facilitates its denaturation with respective alteration of a spectrum of a luminescence of yeast – red colour (λmax = 640 nanometers). Undigested yeast keeps the native form of DNA, that is green colour.The visual estimation of chemotaxis, adhesion and endocytosis has allowed to estimate quantity of phagocyte cells. The phagocytic index was up-to-date of referential values at M and МТ. The minimum value of endocytosis of neutrocytes was revealed in MG group. Insufficiency of digesting ability of neutrophils can lead to negative consequences, if neutrocytes migrate in various tissues of an organism with undigested antigens. The low digesting activity of granulocytic neutrophils has been revealed at patients with МТ (the yeast, which didn’t expose digestion, keptthe native form of DNA and, accordingly, they have green luminescence of constant intensity and light-orange colour). Results of immunofluorescence correspond to data of visual observation of adhesion and endocytosis of phagocyte neutrophils (the first methodical approach – light microscopy). Thelow intensityof formation of active forms of oxygen has been revealed in the NBTR-test according to intensity of oxidation-reduction reactions. The low oxidising reserve of enzymes of neutrophils has been revealed in induced NBTR-test at MG because at this category of patients the spontaneous level of oxidation was in 4 times more than induced one. High frequency and antigenic virus load (CMV) has been revealed at patients with МТ, and maximum persistence VEB has been revealed at MG. Research of presence and processing of antigens, functional oxygen-dependent activityof enzymes of neutrophils and completenessof phagocytosis has revealed various degree of disturbances of barrier function of phagocyte cells, and also change of the titer and frequencies of occurrence of herpes viruses CMV and VEB at various clinical phenotypes of myasthenia. Conclusion. It is shown, that degree of expression and frequency of occurrence of persistence of cytomegalovirus and Epstein-Barra virus are interconnected with defects of various stages of phagocytosis, its completeness and activity of the intracellular enzymes which participate in formation of active forms of oxygen, and intensity of formation of monomers of DNA of the microorganisms which are grasped by phagocytes. Disturbance of barrier function of immunity at myasthenia is significant for a debut and disease advance. An estimation of phagocytosis and virus persistence, as trigger factor of myasthenia, is important for a choice of target therapy. Use of evolutionary scientific methodology of I.I. Mechnikov in the synthetic approach for diagnostics of trigger factors and monitoring of stage of formations of pathological process allows to prove individual medical-diagnostic algorithm for correction of various clinical forms of autoimmune diseases. The approaches for address therapy are proved at various clinical phenotypes of myasthenia which includes carrying out of staged monoligand therapy by peptides and enzymes. This therapy referred on activation of intracellular enzymes of neutrophils at incompleteness of phagocytosis, and application of the immunoglobulins which are specific to herpes viruses.